Multiomic analysis of the synthetic pathways of secondary metabolites in tobacco leaves at different developmental stages - Tong, Zhijun; Yang, Kun; Chen, Xuejun; Xu, Fei; Sui, Xueyi; Huang, Yujie; Zhu, Shenyun; Shen, Enhui; Wu, Sanling; Fan, Longjiang; Xiao, Bingguang (Frontiers in Plant Science, 2025)
IntroductionNicotiana tabacum, widely cultivated for its economic and scientific value, produces a broad range of secondary metabolites that play critical roles in determining leaf quality and flavor. Despite substantial progress, the comprehensive regulatory landscape governing secondary metabolite biosynthesis during N. tabacum leaf development remains largely unclear.MethodsTo better understand the molecular regulatory mechanisms underlying the biosynthesis of secondary metabolites, particularly flavonoids, during N. tabacum leaf development, we conducted a transcriptomic and non-targeted metabolomic sequencing and analysis at three critical developmental stages: vigorous growth stage (T1), topping stage (T2), and harvest stage (T3).ResultsBased on our transcriptomic and metabolomic data, 25 unigenes exhibiting stage-specific expression patterns that were strongly associated with flavonoid accumulation were identified. We found that during early developmental stages (T1-T2), upregulated expression of chalcone synthase (CHS) and chalcone isomerase (CHI) correlated with enhanced flavonoid backbone biosynthesis. In contrast, during the later stage (T3), increased expression of dihydroflavonol 4-reductase (DFR) and anthocyanidin synthase (ANS) was consistent with elevated anthocyanin accumulation.ConclusionThis study systematically analyzed the coordinated regulatory network of flavonoid biosynthesis during leaf development in N. tabacum, revealing dynamic metabolic shifts across developmental stages. The findings offer novel molecular insights into the mechanisms underlying leaf quality formation and establish a theoretical framework for functional studies of candidate genes, reinforcing the utility of N. tabacum as a model species for secondary metabolism research and breeding innovation.